2021
DOI: 10.1016/j.apsb.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of USP7 is an alternative strategy to downregulate PD-L1 and sensitize gastric cancer cells to T cells killing

Abstract: Targeting immune checkpoints such as programmed cell death protein 1 (PD-1) and programmed death ligand-1 (PD-L1) have been approved for treating melanoma, gastric cancer (GC) and bladder cancer with clinical benefit. Nevertheless, many patients failed to respond to anti-PD-1/PD-L1 treatment, so it is necessary to seek an alternative strategy for traditional PD-1/PD-L1 targeting immunotherapy. Here with the data from The Cancer Genome Atlas (TCGA) and our in-house tissue library, PD-L1 expression was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 68 publications
1
51
0
Order By: Relevance
“…USP7 is a deubiquitinase that regulates many diverse cellular processes, including tumor suppression. PD-L1 expression is positively correlated with USP7 expression in gastric cancer [145]. USP7 suppression impairs PD-L1/PD-1 interaction and enhances the cytotoxic reaction of T cells and the anti-tumor immune response [145].…”
Section: Usp7 Upregulates Pd-l1 In Tumorsmentioning
confidence: 99%
“…USP7 is a deubiquitinase that regulates many diverse cellular processes, including tumor suppression. PD-L1 expression is positively correlated with USP7 expression in gastric cancer [145]. USP7 suppression impairs PD-L1/PD-1 interaction and enhances the cytotoxic reaction of T cells and the anti-tumor immune response [145].…”
Section: Usp7 Upregulates Pd-l1 In Tumorsmentioning
confidence: 99%
“…P5091, a tri-substituted thiophene with dichlorophenylthio, nitro, and acetyl substituents mediating anti-USP7 activity, was firstly reported to induce apoptosis in multiple myeloma cells resistant to conventional and bortezomib therapies [ 94 ], and then showed antitumor effect in various cancers, including CRC, ovarian cancer, bladder cancer, prostate cancer and HCC [ 95 , 96 ]. In gastric cancer, depletion of USP7 by p5091 decreased PD-L1 (Programmed Cell Death 1 Ligand 1, also known as CD274) expression and sensitized gastric cancer cells to T cell killing [ 97 ]. Moreover, p5091 was reported to significantly modulate the phenotype and function of M2 (CD11b + F4/80 + CD86 − CD206 + ) macrophages, and combinational treatment of p5091 and Programmed Cell Death 1 (PD1) antibody exerted synergistic anti-tumor effect in lung cancer [ 98 ].…”
Section: Usp7 Inhibitorsmentioning
confidence: 99%
“…It has been reported that the oncogenic signals may disrupt the expression of cell cycle and antigen presentation genes of host cells, thereby leading to abnormal proliferation of CCs in the body and a state of unresponsiveness to the defense mechanisms, respectively ( 27 , 28 ). CCs can decrease the downstream signal stimulation of the TCR and lead to dysfunction or apoptosis of T cells through the upregulation of the immune-suppressive molecule PD-L1 ( 29 ). Michael Karin and Shabnam Shalapour considered abnormal epigenetic modifications of certain molecular phenotypes, namely death receptors, stress-induced ligands, major histocompatibility complex (MHC)-I molecules, intact antigen processing and presentation machinery (APM), and tumor-associated antigens (TAA), all of which play important roles in the development of CC-intrinsic immune evasion capabilities ( 30 ).…”
Section: Chief Features Of Icdmentioning
confidence: 99%